Identification of sound pressure levels in bus station in Goiania - Lauro, Jardel de Castro; Silva, Betina Alaides da; Barros, Rosana Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The public transportation stations in the large cities aim to interconnect the routes of this system, making it more efficient, however, these environments achieve high levels of noise which may cause serious health risks for users. This study has the objective of measuring the sound pressure levels existing in the bus station “Terminal Praça da Bíblia”, located in Goiania, Go and compare them to the current legislation and standards, also investigate the user’s perception of the noise through a questionnaire. The study was conducted in the months of September and October of 2013, in which the equipment used was the decibelmeter during the measurements. Based on the results, it was found that all the values obtained were above the permitted values of the NBR 10151, ranging from 65,8 to 88,8 dB(A). The questionnaires applied to the users of the public transportation system revealed that most of them know about this issue and are being submitted to alarming levels of noise every day. Noise pollution control projects should be created in order to turn possible a harmonious environment, in addition to protect the health of the people who go to the bus station.